Surface-Associated Lipoproteins Link Enterococcus faecalis Virulence to Colitogenic Activity in IL-10-Deficient Mice Independent of Their Expression Levels. - Soeren Ocvirk; Irina G Sava; Isabella Lengfelder; Ilias Lagkouvardos; Natalie Steck; Jung H Roh; Sandrine Tchaptchet; Yinyin Bao; Jonathan J Hansen; Johannes Huebner; Ian M Carroll; Barbara E Murray; et al. (PLoS Pathogens, 2015)
The commensal Enterococcus faecalis is among the most common causes of nosocomial infections. Recent findings regarding increased abundance of enterococci in the intestinal microbiota of patients with inflammatory bowel diseases and induction of colitis in IL-10-deficient (IL-10-/-) mice put a new perspective on the contribution of E. faecalis to chronic intestinal inflammation. Based on the expression of virulence-related genes in the inflammatory milieu of IL-10-/- mice using RNA-sequencing analysis, we characterized the colitogenic role of two bacterial structures that substantially impact on E. faecalis virulence by different mechanisms: the enterococcal polysaccharide antigen and cell surface-associated lipoproteins. Germ-free wild type and IL-10-/- mice were monoassociated with E. faecalis wild type OG1RF or the respective isogenic mutants for 16 weeks. Intestinal tissue and mesenteric lymph nodes (MLN) were collected to characterize tissue pathology, loss of intestinal barrier function, bacterial adhesion to intestinal epithelium and immune cell activation. Bone marrow-derived dendritic cells (BMDC) were stimulated with bacterial lysates and E. faecalis virulence was additionally investigated in three invertebrate models. Colitogenic activity of wild type E. faecalis (OG1RF score: 7.2±1.2) in monoassociated IL-10-/- mice was partially impaired in E. faecalis lacking enterococcal polysaccharide antigen (ΔepaB score: 4.7±2.3; p<0.05) and was almost completely abrogated in E. faecalis deficient for lipoproteins (Δlgt score: 2.3±2.3; p<0.0001). Consistently both E. faecalis mutants showed significantly impaired virulence in Galleria mellonella and Caenorhabditis elegans. Loss of E-cadherin in the epithelium was shown for all bacterial strains in inflamed IL-10-/- but not wild type mice. Inactivation of epaB in E. faecalis reduced microcolony and biofilm formation in vitro, altered bacterial adhesion to intestinal epithelium of germ-free Manduca sexta larvae and impaired penetration into the colonic mucus layer of IL-10-/- mice. Lipoprotein-deficient E. faecalis exhibited an impaired TLR2-mediated activation of BMDCs in vitro despite their ability to fully reactivate MLN cells as well as MLN-derived colitogenic T cells ex vivo. E. faecalis virulence factors accounting for bacterial adhesion to mucosal surfaces as well as intestinal barrier disruption partially contribute to colitogenic activity of E. faecalis. Beyond their well-known role in infections, cell surface-associated lipoproteins are essential structures for colitogenic activity of E. faecalis by mediating innate immune cell activation.